352 ISOLATION OF DISCRETE REGIONS OF THE BRAIN FROM IRON REGULATORY PROTEIN-2 KNOCKOUT MICE. (1st January 2005) - Chin, V.; Snissarenko, E.; Anton, L.; Kim, I.; Mueller, C.; Magaki, S.; Obenaus, A.; Kirsch, W. M.
Abstract : Introduction: Altered brain iron metabolism in the face of aging is cited as a significant risk factor for development of Alzheimer's Disease. In order to correlate brain iron pools (total, loosely bound, non-heme) with novel magnetic resonance imaging (MRI) an experimental mouse model with an engineered deletion of iron regulatory protein-2 (IRP-2) was used. The novel MR sequences are termed susceptibility weighted imaging (SWI). These mice display signs of neurodegeneration after six months of age, manifested by ataxia, vestibular dysfunction, tremors, and postural abnormalities. The purpose of this study was to develop a dissection technique that enabled a standardized and reproducible method to secure regions of interest (ROI) for iron assay measurements. Methods: 35 C57/B1 mice were euthanized with the Muromachi Microwave Fixator. Controlled microwave brain fixation provides immediate fixation of brain metabolites and conservation of iron in its various pools. Craniotomies are performed to expose the underlying fixed brain. We are able to dissect 12 distinct ROI from each hemisphere (5-10 mg in quantities, ww). Results: Our dissection technique allowed isolation of the following ROI: olfactory bulbs, frontal cortex, parietal cortex, cerebellum, hippocampus, nucleus accumbens, striatum, ventral midline basal nucleus, quadrigeminal plate, lower midbrain, entorhinal cortex, and brainstem. The validity of the dissection was verified by the reconstruction of the ROI followed by histological sectioning, and T2 MRI imaging. Conclusions: Controlled brain microwave fixation gives the brain tissue the unique consistency necessary for the successful isolation of distinct ROI. The newly created dissection protocol allows for the: a) identification and removal of 12 such structures, b) sufficient tissues for analyzing amounts of iron or other metabolites, and c) the unique ability to correlate iron content in its various pools with image SWI MRI. The mouse model will form the basis of the interpretation of human brain iron MR determinations.